2017
DOI: 10.1111/jnu.12350
|View full text |Cite
|
Sign up to set email alerts
|

A Multicountry Perspective on Cultural Competence Among Baccalaureate Nursing Students

Abstract: Purpose: To assess cultural competence among nursing students from nine countries to provide an international perspective on cultural competence. Design: A descriptive, cross-sectional design. Methods: A convenience sample of 2,163 nursing students from nine countries was surveyed using the Cultural Capacity Scale from April to November 2016. Results: The study found a moderate range of cultural competence among the students. The ability to teach and guide other nursing colleagues to display culturally appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
3
27
1
6
Order By: Relevance
“…Content validity for this section of the questionnaire was ensured by including questions and answer options based on published work in cultural responsiveness or based on the census data collection in Australia and Aotearoa New Zealand [9, 23, 35, 36]. For example, questions related to demographic variables such as age, gender, level of study, self-identified ethnoculture, type of program or previous cultural training were either adapted from published studies assessing self-perceived cultural responsiveness or constructed based on the literature defining important factors associated with cultural responsiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Content validity for this section of the questionnaire was ensured by including questions and answer options based on published work in cultural responsiveness or based on the census data collection in Australia and Aotearoa New Zealand [9, 23, 35, 36]. For example, questions related to demographic variables such as age, gender, level of study, self-identified ethnoculture, type of program or previous cultural training were either adapted from published studies assessing self-perceived cultural responsiveness or constructed based on the literature defining important factors associated with cultural responsiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies suggest that culturally sensitive education removes differences in terms of healthcare services delivered to patients (Brach & Fraserirector, 2000) and improve healthcare quality so that it should be integrated to nursing curriculum (Waite & Calamaro, 2010;Cruz et al, 2018). However, evaluation of the impact of education on cultural sensitivity is as important as intercultural nursing education itself (Chen & Starosta, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our own research showed a high level of tolerance of the beliefs or behavior of various cultural groups in relation to health/illness and the ability to meet the needs of patients from different cultures by implementing nursing activities, increasing, as other authors indicate, the ability to act beyond cultural barriers [42,68], which include country of residence, gender, age, year of studies, participation in cultural training, experience in caring for patients from other cultures or from special population environments, and living in a multicultural environment [10].…”
Section: Plos Onementioning
confidence: 99%
“…In 2011 there were over 34 million Christians in Poland, forming 88.8% of the population [ 6 ], although the religiosity of young adult Poles is on the decline [ 7 ]. This situation leads to the necessity of having, and therefore of forming, cultural competencies of healthcare workers [ 8 ] such as those in other countries [ 9 , 10 ]. Poland ratified the UNESCO Convention on the Protection and Promotion of the Diversity of Cultural Expressions in 2007, which makes possible an intensification of efforts to develop cultural competencies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%